2021
DOI: 10.3233/ch-200996
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of ballet-type and conventional stent graft configurations for endovascular aneurysm repair: A CFD analysis

Abstract: PURPOSE: Cross limb stent graft (SG) configuration technique for endovascular aneurysm repair (EVAR) is employed for splayed aortic bifurcations to avoid device kinking and smoothen cannulation. The present study investigates three types of stent graft (SG) configurations for endovascular aneurysm repair (EVAR) in abdominal aortic aneurysm. A computational fluid dynamic analysis was performed on the pulsatile non-Newtonian flow characteristics in three ideally modeled geometries of abdominal aortic (AA) SG con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…While in our previous cohort study, which was characterized by the largest sample size and additional subgroup analysis, patients with large aneurysm sac and tortuous iliac arteries encountered fewer type I endoleaks in the CL group ( 22 ). This conclusion was consistent with a recent hemodynamic study revealing that this non-standard configuration could sustain higher wall shear stress and helicity characteristics ( 16 , 17 ). However, it was questioned that it may be modified delivering system, instead of CL, that improved prognosis ( 36 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While in our previous cohort study, which was characterized by the largest sample size and additional subgroup analysis, patients with large aneurysm sac and tortuous iliac arteries encountered fewer type I endoleaks in the CL group ( 22 ). This conclusion was consistent with a recent hemodynamic study revealing that this non-standard configuration could sustain higher wall shear stress and helicity characteristics ( 16 , 17 ). However, it was questioned that it may be modified delivering system, instead of CL, that improved prognosis ( 36 ).…”
Section: Discussionsupporting
confidence: 93%
“…For efficacy of the CL in practice, however, related studies have drawn inconsistent conclusions, which makes the true effect of CL doubtful. By analysis of computed fluid dynamics, CL showed a tendency to prevent stent thrombosis, accompanied by tolerance for higher wall shear stress and helicity characteristics ( 16 , 17 ). On the contrary, long-term fatigue and displacement implications were revealed by the same studies and another one demonstrated that it was the angle of the aneurysm neck other than the configuration that affected hemodynamic index ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the postoperative outcomes of this technique have yet to be clarified, and no indications or contraindications have been described. A recent study has shown that this configuration supported high wall shear stress and helicity characteristics [ 11 , 12 ]. Alternatively, brachial access can be performed, but this approach is associated with several complications, such as bleeding and thrombosis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the extensive utilization of EVAR in managing rAAA, the choice of endovascular stents, as a critical determinant, can significantly impact surgical procedures and prognostic outcomes ( 7 , 8 ). Presently, a variety of endovascular stents with distinct characteristics and delivery platforms are available for EVAR implementation.…”
Section: Introductionmentioning
confidence: 99%